Case report: Recreational nitrous oxide abuse triggered peripheral neuropathy possibly through the immune-mediated pathogenesis - Dong, Mei-Xue; Wang, Qing; Xu, Jun-Feng; Hu, Ling; Yu, Ying; Li, Tao (Frontiers in Neurology, 2022)
Nitrous oxide (N2O), commonly known as laughing gas, is widely used in clinical practice and food industry. However, an increasing number of young people have been abusing N2O for recreation, resulting in many functional disorders and sometimes irreversible nerve damage. We present the case of a 20-year-old N2O abuser who developed peripheral neuropathy after continuing inhaling N2O for two months. The neurological symptoms of the patient had kept exacerbation for the next two months until she came for medical care sitting in a wheelchair. We suggested the patient halting N2O intake and supplementing methylcobalamine according to the standardized protocol. Her symptoms had partly recovered during the following two weeks but remained unchanged in another two weeks. Antibodies against ganglioside complexes were detected and anti-GM1 ganglioside (IgM type) was positive in both cerebrospinal fluid and serum. Intravenous immunoglobulin was given as an additional treatment and the patient’s symptoms had significantly recovered further. The patient discharged walking by herself. With this case we were able to show that N2O-related peripheral neuropathy is not only a metabolic disorder but also an immune-mediated disease. N2O intake can trigger a mimic Guillain-Barré syndrome.